Does AI Respect Patient Privacy Adequately? A Critical Examination of Digital Health Ethics - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2021)
Does AI Respect Patient Privacy Adequately? A Critical Examination of Digital Health Ethics The integration of Artificial Intelligence (AI) into healthc...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine